2018
DOI: 10.1007/s12325-018-0667-3
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Evaluation of Direct and Indirect Economic Burden Among Endometriosis Patients in the United States

Abstract: IntroductionThe prevalence of endometriosis and the need for treatment in the USA has led to the need to explore the contemporary cost burden associated with the disease. This retrospective cohort study compared direct and indirect healthcare costs in patients with endometriosis to a control group without endometriosis.MethodsWomen aged 18–49 years with endometriosis (date of initial diagnosis = index date) were identified in the Truven Health MarketScan® Commercial database between 2010 and 2014 and female co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(119 citation statements)
references
References 23 publications
(29 reference statements)
5
103
0
4
Order By: Relevance
“…Patients had an average of 11.7 all-cause annualized ambulatory visits, 0.8 all-cause annualized emergency visits, and 0.1 all-cause annualized inpatient stay during the 60-month pre-diagnosis period. Similarly, Soliman et al [17] reported that patients with endometriosis averaged 9.9 office/obstetrics-gynecology visits, 0.6 emergency visits, and 0.1 inpatient admissions in the 12 months prior to diagnosis. Utilization of healthcare services was also comparable to results described by Fuldeore et al [18] who found emergency visits, outpatient visits, and physician visits increased over a 5-year period prior to endometriosis diagnosis peaking in the year immediately prior to diagnosis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Patients had an average of 11.7 all-cause annualized ambulatory visits, 0.8 all-cause annualized emergency visits, and 0.1 all-cause annualized inpatient stay during the 60-month pre-diagnosis period. Similarly, Soliman et al [17] reported that patients with endometriosis averaged 9.9 office/obstetrics-gynecology visits, 0.6 emergency visits, and 0.1 inpatient admissions in the 12 months prior to diagnosis. Utilization of healthcare services was also comparable to results described by Fuldeore et al [18] who found emergency visits, outpatient visits, and physician visits increased over a 5-year period prior to endometriosis diagnosis peaking in the year immediately prior to diagnosis.…”
Section: Discussionmentioning
confidence: 90%
“…Patients with endometriosis experience significant healthcare expenses. In a study of endometriosis patients and matched controls, mean annual adjusted direct healthcare costs were more than three times higher in endometriosis patients than controls during the 12 months following diagnosis ($16,573 versus $4733, p \ 0.005) [17]. Fuldeore et al found that costs were highest in the first year following an endometriosis diagnosis, costing $13,199 compared with $6041 in the year prior to diagnosis and $6720 in the year following the index year.…”
Section: Introductionmentioning
confidence: 98%
“…In addition to potentially painful symptoms and significant healthcare costs [7,8], endometriosis is associated with increased work absenteeism and decreased productivity [9]. A Danish survey study compared 610 employed patients with endometriosis with 751 control patients and reported that those with endometriosis had significantly more sick days, work disturbance due to symptoms, and lower work ability (attributed to pain and tiredness) [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective cohort study, Soliman et al [15] found that women with endometriosis had significantly higher direct healthcare costs, as well as indirect costs due to work loss through absenteeism and short-or long-term disability relative to control participants without a history of endometriosis. As underlined by Hummelshoj [16], treatment costs account for only one third of the total annual economic burden of endometriosis (estimated at EUR 9579 per woman [11]) because two thirds of this cost is caused by productivity loss due to pain symptoms [11,17].…”
Section: Introductionmentioning
confidence: 99%